Zuelzer Wilson syndrome with Waardenberg syndrome: A morbid combination of Neurocristopathies - Rishitha Reddy, Gaddam; B, Khanagavi, Bhagyajyothi; B Kurbet, Santosh; S Koujalagi, Ramesh (Journal of Neonatal Surgery, 2025)
Neurocristopathy refer to a diverse group of congenital disorders that arise due to defects in the migration, growth or specialization of neural crest cells during early embryonic development. These cells contribute to the development of melanocytes, enteric ganglia, and autonomic nervous system structures. We report a rare and complex case of neonate with combination of Waardenburg syndrome with Zuelzer-Wilson syndrome both united by a defective neural crest development (1,2). The neonate was brought on the fifth day of life with progressive abdominal distention, bilious vomiting, and an absence of meconium passage since birth. Clinical features were indicative of a lower gastrointestinal obstruction. The notable features included a white forelock, anisocoria, and multiple de-pigmented macules all pointing towards a diagnosis of Waardenburg's syndrome. The patient Underwent contrast study suggestive of Hirschsprung's disease. Surgical exploration and histopathological livering biopsies revealed total colonic agenesis with consistent with Hirshsprung's disease of syndromic origin with Zuelzer-Wilson syndrome. The consistence of these two disorders in a single patient is rare and represents a massive failure of neural crest migration. This case highlights the importance of detailed physical examination and early surgical and genetic evaluation in neonates with multisystemic manifestations of neural crest dysfunction early.